Nano drug deliverer for ampicillin, clavulanic acid, imipenem, penicillin g and ticarcillin - Derakhshandeh, Maryam; Monajjemi, Majid (Nexo Revista Científica, 2020)
Ampicillin belonging to the penicillin group of beta lactam antibiotics. Ampicillin is able to penetrate Gram positive and some Gram-negative bacteria. Imipenem (Primaxin) is an intravenous β-lactam antibiotic discovered by Merck scientists Burton Christensen, William Leanza, and Kenneth Wildonger in 1980 Ampicillin, Clavulanic acid, Imipenem, Penicillin G and Ticarcillin properties for the drug delivery with binding to SWCNNTs and SWBNNTs have been studied. Penicillin and its alteration Penicillin G or phenoxyacetic acid for Penicillin V is used for large scale production. Penicillin and other cell wall inhibitors are primarily specific against Gram positive bacteria because of higher percentage of peptidoglycan in the cell walls of these organisms. It was the first member of the carbapenem class of antibiotics. Based on our previous works we have modeled and simulated a drug delivery system of those antibiotics. The investigation of those antibiotics in binding with single-walled carbon nanotube (SWCNT) and SWBNNTs have been studied by theoretical methods. It has been established the best structural and functional of those antibiotics.